2021
DOI: 10.1111/ecog.05582
|View full text |Cite
|
Sign up to set email alerts
|

Towards an understanding of the latitudinal patterns in thermal tolerance and vulnerability of woody plants under climate warming

Abstract: Predicting spatial patterns in thermal tolerance and vulnerability of species under climate warming remains a challenge. Current knowledge is mainly from experiment‐based thermal physiology of limited numbers of ectotherms, yet large‐scale evaluations on plants remain elusive. Here, using distribution maps with spatial resolutions of 20 × 20 km for 5628 woody species in China, we propose a novel approach, i.e. thermal distribution curves, to describe species' realized thermal niches and then estimate their the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…However, as shown in Table 1, from families to genera to species, with the decrease in the taxonomic level, the correlation and interpretation degree of the mean value of various climatic factors to the diversity rapidly decreased. It is possible that the ecological range of plant species is narrower, while the ecological range of plant families and genera is wider, which is consistent with a gradual decrease in plant threat levels with increasing latitude (Peng et al, 2021). Fluctuations in the external environment may allow plant species to acquire higher tolerance in order to cope with the effects of unfavorable conditions on themselves (Zhang and Tielbörger, 2019;Perez and Feeley, 2021).…”
Section: Discussionmentioning
confidence: 88%
“…However, as shown in Table 1, from families to genera to species, with the decrease in the taxonomic level, the correlation and interpretation degree of the mean value of various climatic factors to the diversity rapidly decreased. It is possible that the ecological range of plant species is narrower, while the ecological range of plant families and genera is wider, which is consistent with a gradual decrease in plant threat levels with increasing latitude (Peng et al, 2021). Fluctuations in the external environment may allow plant species to acquire higher tolerance in order to cope with the effects of unfavorable conditions on themselves (Zhang and Tielbörger, 2019;Perez and Feeley, 2021).…”
Section: Discussionmentioning
confidence: 88%
“…Following the IPCC 2022 conceptual framework for risk assessment (Pörtner et al, 2022), the risk of decline of tree taxa was inferred by comparing species aridity niches and range size, reflecting vulnerability, with predicted aridity changes, reflecting exposure. Our methodology to quantify exposure and vulnerability is based on density of occurrences curves across the aridity gradient (Figure 1) and has been previously used to estimate species responses to climate change (Peng et al, 2021; Wooliver et al, 2022). It has been demonstrated that niche metrics as well as range size are crucial to estimate vulnerability to climate change (Thuiller et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Also, it has been shown that increase in the frequency of extreme events such as hotter droughts, can lead to large‐scale tree die‐off (Allen et al, 2010; Hammond et al, 2022). In addition, some tree species might occur in areas where climatic conditions are already reaching their tolerance limits (Lancaster & Humphreys, 2020; Sentinella et al, 2020), particularly in arid environments (Peng et al, 2021). However, predictions of changes in aridity conditions are highly variable on a regional scale (Huang et al, 2017; Lin et al, 2018; Park et al, 2018), with some warm drylands and deserts expected to experience even more rainfall than today, such as in the Sahara Desert (Pausata et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Species distributions and habitat areas represent the constraints and dispersal effects of environmental factors ( Brown et al., 1996 ). The effects of factors such as temperature, CO 2 concentration and climate on the growth of woody plants have been the subject of several studies ( Zanne et al., 2014 ; Baig et al., 2015 ; Zhang et al., 2016 ; Liu et al., 2018 ; Peng et al., 2021 ). To further investigate the effects of climate change on plant distribution dynamics, several research have used species distribution models (SDMs) to simulate changes in the geographic distributions and areas of plants ( Guisan and Thuiller, 2005 ; Alo and Wang, 2008 ; Valavi et al., 2022 ) to study the effects on species distribution patterns, which is essential for developing strategies for future biodiversity conservation ( Bellard et al., 2012 ).…”
Section: Introductionmentioning
confidence: 99%